Pengaruh Strategi Point of Purchase Terhadap Keputusan Pembelian pada Indomaret Tallunglipu Kabupaten Toraja Utara - Braselia Palambi; Jens Batara Marewa; Mince Batara (CV. Ulil Albab Corp, 2024)
The problem of this research is how the point of purchase influences purchasing decisions at Indomaret Tallunglipu, North Toraja Regency. The aim of this research is to find out the point of purchase strategy for purchasing decisions at Indomaret Tallunglipu, North Toraja Regency. The method used in this research is a quantitative descriptive method. The data collection techniques in this research are through observation, questionnaires and documentation. Data analysis techniques use quantitative descriptive analysis methods, and use questionnaires for Indomaret Tallunglipu consumers. The results of this research show that the opinions of several consumers about the strategy provided are proven by the questionnaires given and the answers to each alternative are an average of 90%, so it can be said that the POP strategy has had an influence on consumers of Indomaret Tallunglipu, North Toraja Regency